Removal of Dyes in Wastewater Using Pitch-based Carbon Waste Modified with Polyethylenimine - Byeong-Chan Min; Su Bin Kang; Gwang-II Ko; Sung Wook Won (Chemical Engineering Transactions)
In this study, pitch-based carbon (PC) was modified with polyethylenimine (PEI) to produce PEI-modified PC (PEI-PC) for wastewater treatment. PEI, containing amine groups, shows advantages in adsorbing ionic dyes. The adsorption and desorption properties of PEC-PC for dyes were evaluated through pH edge, experiments, adsorption kinetics, isotherm studies, and desorption tests. We selected Cibacron Brilliant Yellow 3G-P (Reactive Yellow 2: RY2) as the model dye for our study. pH edge experiments were conducted in a pH range of 2-12 with an initial dye concentration of 100 mg/L. The results showed that dye uptake on PEI-PC increased as the pH value decreased. Adsorption kinetic experiments confirmed that adsorption equilibrium at pHs 2 and 7 was achieved within 30 min. The adsorption isotherm experiments, conducted at initial dye concentrations ranging from 10 to 300 mg/L, revealed that the experimental data fit well with the Langmuir model. The dye-loaded PEI-PC was desorbed using a 0.05 M NaOH solution, and this adsorption-desorption process was repeated. It was observed that when the adsorption-desorption cycles were repeated from 1 to 5 times, the adsorption efficiency decreased by 29 %.